Problem Dan Tantangan Pembelajaran Bahasa Arab Di Pondok Pesantren Daarut Tauhid Bandung - Wafa Nazli; Aliifah Nabila Putri; Insi Mardiyyah; Muhammad Alfath; Ahmad Fu’adin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article explains the idea of learning Arabic at the Daarut Tauhid Islamic Boarding School in Bandung. Covering the challenges and problems of learning Arabic experienced by students at the Daarut Tauhid Islamic Boarding School, this research aims to enable us to find out what challenges students experience when studying Arabic in the current era of modernization. The method used in this article is a qualitative descriptive method. There are several problems and challenges in learning Arabic, namely internal factors and field learning factors. However, all this does not reduce the enthusiasm of Daarut Tauhid students in learning Arabic. This is proven by continuing to participate in language programs to make it easier for students to memorize the Al-Qur'an at the Daarut Tauhid Islamic Boarding School. This research also has the benefit of letting students know what the challenges and advantages are in learning Arabic and solutions for an educational institution that wants its students to be able to master Arabic. It is also hoped that this research will increase interest for students who have obstacles in learning and practicing Arabic. It is also hoped that educational institutions can find a solution so that teachers and students can support each other in their Arabic language learning. The results of the research show that learning Arabic requires more effort and interest on your part to be able to master Arabic.